Supporting social interactions to improve MOOC participants’ learning outcomes: a literature review - Loh, Hong Sen; Martins van Jaarsveld, Gabrielle; Mesutoglu, Canan; Baars, Martine (Frontiers in Education, 2024)
Introduction The need for more scalable, accessible and affordable education, coupled with technological advancements in information sharing technology and collaborative platforms has led to the growth of MOOCs (massive open online courses). The growth of MOOCs has resulted in learning becoming increasingly distributed, affordable and flexible compared to traditional classroom education, allowing individuals in disadvantaged groups to access high quality educational materials. However, new challenges emerge, most notably with MOOCs’ low completion rates. Among the reasons for a low completion rate, lack of interaction with peers is cited as a major reason, yet, interventions to promote social interaction has received relatively less attention. From a constructivist perspective, social interactions among peers are essential in helping individuals learn. This systematic literature review aimed to understand social interaction interventions in MOOC settings. This includes constructs measured as learning outcomes and how they were measured. Methods Literature articles were sourced from multiple databases and filtered for inclusion using the PRISMA process and its four phases. Twenty articles were included in the final review. Results Results of the review showed that social interactions fall into three categories: discussion forums, learning groups and one-to-one interactions with peers. Learning outcomes investigated were grouped into four categories: knowledge, social engagement, learning engagement and learner experience. Conclusion Across the studies, there were clear positive effects of social interaction on learning outcomes. Intervention strategies include sending prompts for individuals to use discussion boards and also grouping learners by homogeneity based on their learning engagement. However, more experimental studies are necessary to bolster the evidence of a causal impact of social interactions. Also, further research should be done to understand potential mediating factors that contribute to the success of implementing social interactive elements in MOOCs.